Improving the scientific and methodological apparatus for determining the optimum strategy when selecting a grouping element for performing the task - Maistrenko, Oleksandr; Khoma, Vitalii; Kurban, Volodymyr; Savelіev Andrii; Shcherba, Andrii; Karavanov, Oleksandr; Sivak, Oleksandr; Kaliaiev, Oleksii; Isenko, Vitaly; Kosovtsov, Yurii (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is the process of determining the optimal strategy for choosing a certain element of the grouping to perform a certain task. The problem solved was the contradiction between the need to take into account various types of adverse conditions when determining the optimal strategy for assigning a certain type of forces and means for a certain task to the existing approach to maximizing the result. The improved scientific and methodical apparatus includes optimal selection criteria and an improved procedure for optimal selection of a certain grouping element. Existing approaches to the selection of optimal strategies for assigning forces and means to perform tasks were analyzed, in particular the criteria of Wald, Hurwitz, and Savage. The peculiarity of this analysis is the examination of the criteria in view of the types of adverse conditions they take into account. The application of these criteria will make it possible to take into account the conditions of uncertainty of the input data and minimize the influence of adverse conditions during distribution. The field of practical use of the analysis results is management processes during preparation for the operation. A procedure of optimal selection of a certain element of the grouping for the performance of a certain task has been improved by using several criteria for choosing the optimal strategy and harmonizing the results of this selection in accordance with the conditions. The proposed procedure guarantees the performance of tasks, and the increase in the value of the objective function can reach 40 %. A feature of the proposed procedure is that the result of choosing the optimal strategy is determined according to the conditions of a certain operation and takes into account various types of adverse conditions. This makes it possible to take into account the factors that significantly affect the uncertainty and minimize the expenditure of resources when performing a certain set of combat tasks. The scope of practical use of the methodology is the process of planning and allocation of forces and means among tasks in the operation.